Ground state solutions of nonlocal equations with variable exponents and mixed criticality - Yuhang Long; Xingwen Chen; Qiongfen Zhang (Boundary Value Problems)
Abstract In this article, we use approximation techniques and variational methods to study a class of nonlocal equations with variable exponents and mixed criticality. We prove the existence of the ground state nontrivial solutions with the least energy. Our results are applied to a specific Schrödinger-Poisson type system.